IMPLICATIONS OF MATRIMONIAL OFFENCES TOWARDS THE FAMILY INSTITUTION IN THE ERA OF GLOBALISATION - Nur Sarah Tajul Urus; Alias Azhar (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This paper debates the implications of matrimonial offenses on the family institution. The offence of pronouncing talaq (divorce utterance) outside the court is chosen instead of the other two matrimonial offences, which are underage marriage and polygamy without consent. The choice is due to the practice of pronouncing talaq outside the court being an infringement of the existing legal procedure. This issue is raised when the divorce application procedure, which requires talaq to be pronounced in court, continues to be questioned by religious groups and society who are skeptical of the Islamic family law currently in force in the country. The objectives of this article are first, to identify the legal provisions related to divorce application procedure according to its application in Malaysia as well as the role of the Advisory Unit under the Administration of Family Law Division, Kelantan Islamic Affairs Department at Lundang, Kota Bharu, Kelantan. Second, this paper aims to analyse the implications that can be expected if talaq is not pronounced in court and the catalyst for the occurrence of this phenomenon. Third, the paper suggests that religious groups and society be more open in the era of globalisation by considering the maslahah and public interest in general. This study used qualitative data that were gathered through document analysis and interviews. Data analysis was performed by adopting a descriptive approach using content analysis. The finding of the study showed the existence of global impacts on the family institution arising from the offence of pronouncing talaq outside the court. Thus, it is hoped that religious groups and legal experts can work together to create elements of innovation and reduce misunderstandings between the shariah law and legislation that is in force. Awareness and empowerment of law compliance should be implemented collectively so that compliance of the existing law is achieved with deep understanding and awareness. Furthermore, messages conveyed by the religious groups should be consistent and not in conflict with the law that is currently in force.